2017
DOI: 10.3945/jn.116.246710
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary Methionine Restriction Regulates Liver Protein Synthesis and Gene Expression Independently of Eukaryotic Initiation Factor 2 Phosphorylation in Mice

Abstract: The phosphorylation of eukaryotic initiation factor 2 (p-eIF2) during dietary amino acid insufficiency reduces protein synthesis and alters gene expression via the integrated stress response (ISR). We explored whether a Met-restricted (MR) diet activates the ISR to reduce body fat and regulate protein balance. Male and female mice aged 3-6 mo with either whole-body deletion of general control nonderepressible 2 () or liver-specific deletion of protein kinase R-like endoplasmic reticulum kinase () alongside wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 65 publications
8
52
0
Order By: Relevance
“…Although we are not the first to examine the metabolic effects of dietary methionine in both male and female mice (52), to our knowledge, our study is the first to show that sex‐dependent mechanisms may be involved in mediating the effects of dietary methionine on metabolic health. As outlined in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Although we are not the first to examine the metabolic effects of dietary methionine in both male and female mice (52), to our knowledge, our study is the first to show that sex‐dependent mechanisms may be involved in mediating the effects of dietary methionine on metabolic health. As outlined in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The expected result of either too little ternary complex or an ineffective ternary complex is that the 48S complex would be unable to form or to recognize the correct start site. Another possibility is that a decrease in ternary complex formation occurs due to a decrease in eIF2B guanine nucleotide exchange that is not dependent on eIF2 phosphorylation, as has been reported in liver of Gcn2 -null mice fed a methionine-restricted, cysteine-free diet 36 .…”
Section: Discussionmentioning
confidence: 88%
“…Despite a number of studies looking at the effects of starvation of total amino acids, few studies have compared the effects of deficiencies of different single essential amino acids on protein synthesis. In rats and mice, single essential amino acid deprivation can affect hepatic polysome profiles 27 30 , rates of hepatic protein synthesis 30 , 31 , and the phosphorylation status of 4EBP1 27 , 30 32 and eIF2 29 – 31 , 33 36 . Studies in hepatocytes or HeLa cells demonstrated effects of short-term starvation of single amino acids on protein synthesis, polysome formation, and PIC formation 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the inhibition of protein synthesis also could be explained by the lack of the building blocks for making more protein in plasma, specifically methionine ( Tables 1 and 2 ), because it can be the main limiting one to start all translation processes, but it also can act through a mechanism independent of the Met–transfer RNA charging, the activation of a transcriptionally regulated mechanism via the activating transcription factor-4. 106 , 107 , 108 It is worth noting that when all the AAs from the diet were removed, insulin levels were not affected ( Figure 7 ). The amino acid imbalance created by the No Leu diet seems to be the main event that triggers the inhibition of digestive enzyme synthesis after feeding the No Leu diet, and not the lower insulin levels.…”
Section: Discussionmentioning
confidence: 97%